LEGAL POLICY ON REGULATING THE ACCELERATION OF DEVELOPMENT IN DISADVANTAGED REGIONS IN THE IMPLEMENTATION OF NATIONAL DEVELOPMENT WITH A COLLABORATIVE GOVERNANCE APPROACH - Jenar, Saptono (Faculty of Law Universitas Padjadjaran, 2023)
According to National Medium-Term Development Plan for 2020-2024 (RPJMN 2020-2024), there are still 62 regencies specified as disadvantaged regions. The emergence of these disadvantaged regions is empirically a result of uneven national development in the past. Therefore, an affirmation policy from the government is needed to accelerate the development in disadvantaged regions through an acceleration program. The essence of forming regulations to accelerate the development of disadvantaged regions will be examined using a legal and conceptual approach. The discussion in this study is related to the legal politics of forming regulations to accelerate the development of disadvantaged regions, which is an integral part of the implementation of national development. The results of this research indicate that the legal politics of regulating the acceleration of development in disadvantaged regions in the implementation of national development is a mandate of the 2005-2025 RPJPN Law, Regional Government Law, and Ministry of State Law, which is aimed at providing development preferentially to disadvantaged regions and implemented to include the fulfillment of basic needs as well as basic facilities and infrastructure in disadvantaged regions in order to achieve public welfare through equitable development in Indonesia. Concurrently, accelerating development in disadvantaged regions through the implementation collaborative governance approach is a government policy aimed at creating synergy and integrating programs and activities executed by relevant ministries/agencies and partnering with communities and businesses to support funding for the accelerating development in disadvantaged regions.